2010
DOI: 10.1097/mbc.0b013e32833894eb
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent deep vein thrombosis and pulmonary embolism in a young man with Klinefelterʼs syndrome and heterozygous mutation of MTHFR-677C>T and 1298A>C

Abstract: Klinefelter's syndrome is characterized by hypogonadism and infertility and commonly has an XXY karyotype. Within the population of men with this disorder, there is an increased incidence of venous thromboembolic disease. Although the precise mechanisms underlying this prothrombotic state have not been elucidated, it is thought that the increased incidence of thromboembolism is associated with a hypofibrinolytic state secondary to androgen deficiency. We present the case of a 26-year-old man with Klinefelter's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…However, lowering homocysteine levels does not reduce the rate of subsequent DVT. 3 Our patient was found to have MTHFR-C677T and MTHFR-A1298 heterozygous mutations with a normal homocysteine level. 10,11 Angel et al 3 reported a 26-year-old man with Klinefelter's syndrome who had 3 episodes of DVT and pulmonary embolism despite warfarin and dalteparin therapy.…”
Section: Klinefelter's Syndrome and Mthfr Mutationsmentioning
confidence: 63%
See 1 more Smart Citation
“…However, lowering homocysteine levels does not reduce the rate of subsequent DVT. 3 Our patient was found to have MTHFR-C677T and MTHFR-A1298 heterozygous mutations with a normal homocysteine level. 10,11 Angel et al 3 reported a 26-year-old man with Klinefelter's syndrome who had 3 episodes of DVT and pulmonary embolism despite warfarin and dalteparin therapy.…”
Section: Klinefelter's Syndrome and Mthfr Mutationsmentioning
confidence: 63%
“…These have included heterozygous mutations of the G20210A genes, 2 MTHFR-genes, 3 factor V Leiden prothrombin mutation, 4 increased activity of factorVIII:C 5 and antiphospholipid antibody (APLA) syndrome. These have included heterozygous mutations of the G20210A genes, 2 MTHFR-genes, 3 factor V Leiden prothrombin mutation, 4 increased activity of factorVIII:C 5 and antiphospholipid antibody (APLA) syndrome.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…It was noted that KS could also be considered to be a cause of recurrent VTE. In this case, oral anticoagulant therapy for life should be implemented in patients experiencing thromboembolic events [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the high rate of thromboembolic disease in KS, no one has systematically explored the etiology of this phenomenon, and much of our current knowledge is limited and based on single cases or studies with small sample sizes. 4 9 Currently, there are 8 hypotheses describing the pathoetiology of thromboembolism in KS: (1) vascular abnormalities, 33 36 (2) hypofibrinolysis with increased activity of PAI-1, 37 41 (3) high factor VIII, 42,43 (4) platelet hyperaggregability, 44,45 (5) protein C and S deficiency, 9,46 52 (6) high homocysteine, 8 (7) antithrombin III deficiency, 53 and (8) Factor V Leiden heterozygosity. 4,7,54 We speculate that the development of VTE in KS is influenced by the duration and consistency of TRT beginning, for the most part, during adolescence, in contrast to less consistent and much shorter duration of therapy in adult hypogonadal men, typically begun in mid to late adulthood.…”
Section: Discussionmentioning
confidence: 99%